The Relationship between Spirituality and Stress: A Study of Medical Students at Islamic Universities in Jakarta - Syahidah Rena (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
Purpose – The study aims to analyze the relationship between spirituality and academic stress among medical students. Design/method/approach – This study is field research with 225 subjects from UIN Syarif Hidayatullah (n = 115) and YARSI University (n = 110). The data collection instrument used two psychological scales, namely the spirituality scale and the stress scale. The data were analyzed using regression analysis techniques. Findings – The results showed that most students tended to experience moderate stress (n = 134), however, the number of students who experienced severe stress was greater than those with mild stress (n = 53 ‘severe stress’ > n = 38 ‘mild stress'). These results indicate that students should have a self-defense mechanism, namely spirituality. Moreover, the study found that spirituality had a significant negative relation with stress in medical students (r = -0.123, p = 0.00 and R2 = 0.263). It means that the higher the student’s spirituality, the lower the level of academic stress. The significance of the relationship between spirituality and academic stress has confirmed that spirituality in medical students serves as a form of self-protection mechanism to deal with factors that can trigger academic stress. However, the contribution of spirituality to stress was only 26.3%, while the rest (73.7%) were influenced by other variables outside this study. Low r and R2 scores also indicated that in dealing with academic stress, students rely not only on internal defense resources but also on external social and environmental supports. Research implications/limitations – This research has implications for promoting prevention programs designed by universities to improve the student’s ability to overcome obstacles during their medical learning process, such as involving the dimension of spirituality in managing the mental well-being of medical students in dealing with academic pressure. Originality/value – This research has significance in providing additional understanding of the positive impact of spirituality on the context of learning. The findings of this study have emphasized the importance of educational institutions paying attention to student self-protection mechanisms to prevent personal difficulties. The results showed that spirituality has a significant role in relieving stress in medical students.